A Synopsis of the family Pottiaceae in Brazil - Costa, Denise Pinheiro Da (Phytotaxa, 2016)
The Pottiaceae are acrocarpous mosses, with South America being considered one of the centers of diversity. A revision of Brazilian species of the Pottiaceae resulted in 66 accepted species in the subfamilies Timmielloideae, Trichostomoideae, Barbuloideae, and Pottioideae. These species are found at elevations from sea level to 2700 m in Brazil. The family itself consists of 36 genera and 66 species, with only six taxa being considered endemic. Two new synonyms are designated for Weissia controversa: Weissia submicacea and Trichostomum exulatum. An illustrated key is presented for all the Brazilian species of the family Pottiaceae, as well as the vegetation types where they occur, there altitudinal ranges in Brazil, substrate types, world distributions, and additional comments.